Synthesis and application of gold nanoparticles as antioxidants - Babay Asih Suliasih; Setia Budi; Haliza Katas (Pensoft Publishers, 2024)
Non-communicable diseases (NCDs) and premature aging, caused by free radicals, have spurred a demand for extensive research into finding effective antioxidants. Currently, there is an abundance of both natural and synthetic antioxidants, including metal nanoparticles with high antioxidant activity. Among these, gold nanoparticles (AuNPs) stand out as favoured antioxidants because of their minimal toxicity, simple synthesis, and detectability. The antioxidant properties of AuNPs enhance its wide-ranging potential for use in healthcare including applications as anti-aging, anti-inflammatory, and wound healing agents, as well as treatment for various diseases. This review highlights recent progress in the synthesis of AuNPs as antioxidants and method for assessing their antioxidant capacity as well as delves into their mechanism of action and explores their potential health applications. In conclusion, considering the physicochemical and biological properties, along with the benefits and potential challenges for future development, AuNPs are deemed promising and effective antioxidants suitable for clinical applications.